Determinant Factor on the Decision to Use the COD Payment Method : Case of Millennial Generation - Indonesia - Haryudi Anas (East Asian Journal of Multidisciplinary Research, 2023)
This research is to determine the effect of promotion, service quality and trust on the decision to use the e-commerce cash on delivery (COD) payment method for the millennial generation in the city of Bekasi. In this study using quantitative and descriptive research methods in which the Millennial Generation in the city of Bekasi is the object. In this study using a purposive sampling technique and using a sample of 95 respondents. The design used in this study is hypothesis testing using the structural equity model (SEM) – SmartPLS 4.0. The results of this study indicate that the three variables namely Promotion, Service Quality and Trust have an influence on the decision to use the e-commerce cash on delivery (COD) payment method for millennials in the city of Bekasi.. This research has limited research objects which only use 95 Millennials in the city of Bekasi as research respondents. This is used as a suggestion for further researchers. The novelty in this study combines the variables Effect of Promotion, Service Quality and Trust on Decisions to Use the e-commerce cash on delivery (COD) payment method for millennials in the city of Bekasi.